Politics and confidence toward the COVID-19 vaccination: A Brazilian cross-sectional study - Marco Antonio Catussi Paschoalotto; Joana Cima; Eduardo Costa; Sara Valente de Almeida; Joana Gomes da Costa; João Vasco Santos; Claudia Souza Passador; João Luiz Passador; Pedro Pita Barros (Taylor & Francis Group, 2024)
ABSTRACTThis study has the aim of assessing the Brazilian perceptions, influencing factors and political positioning on the confidence concerning COVID-19 vaccination. To achieve the objective, the methods rely on a cross-sectional survey of Brazilian citizens, distributed through different social networks. The sample is composed of 1,670 valid responses, collected from almost all Brazilian states and state capitals. To analyze the data and give a clear view of the variables' relationship, the study used bivariate and comparative graphs. Results show a higher level of confidence in vaccines from Pfizer and AstraZeneca, while the lower level of confidence is associated with vaccines from Sinopharm and Sputinik5. Vaccine efficacy is the most significant influencing factor that helps in the decision to get vaccinated. Also, individuals are less willing to get vaccinated if their political preferences are related to the right-wing. The results led to three main health and social implications: i) the vaccination strategy campaigns should take in count vaccine efficacy and political aspects; ii) the vaccination process should be adapted to regions with different political positions; and iii) a reinforcement in the educational policies of the vaccine's importance to the public health, to avoid the politization of a health issue.